PENGARUH CITRA MEREK, GAYA HIDUP, E-WOM & KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA KAFE SEARAH DI KOTA SAMARINDA - Novel Reonald; Fikta Novia Ayu Safitri; Desy Fitriani (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2025)
This study aims to determine the influence of brand image, lifestyle, electronic word of mouth (e-WOM), and service quality on consumer satisfaction at Searah Cafe in Samarinda City. This study uses a quantitative approach with data collection techniques through distributing questionnaires to 95 respondents who are consumers of Searah Cafe. The data analysis technique used is multiple linear regression analysis with the help of SPSS version 30 software.The results of the study indicate that simultaneously the variables of brand image, lifestyle, e-WOM, and service quality have a significant effect on consumer satisfaction. Partially, the four variables of brand image, lifestyle, e-WOM, and service quality have a positive and significant effect on consumer satisfaction. These findings indicate the importance of strengthening brand image, adapting consumer lifestyles, improving service quality, and utilizing e-WOM positively to increase consumer satisfaction.